2014
DOI: 10.1371/journal.pone.0092088
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exercise Leads to Regulation of Telomere-Associated Genes and MicroRNA Expression in Immune Cells

Abstract: Telomeres are specialized nucleoprotein structures that protect chromosomal ends from degradation. These structures progressively shorten during cellular division and can signal replicative senescence below a critical length. Telomere length is predominantly maintained by the enzyme telomerase. Significant decreases in telomere length and telomerase activity are associated with a host of chronic diseases; conversely their maintenance underpins the optimal function of the adaptive immune system. Habitual physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 103 publications
0
98
1
1
Order By: Relevance
“…As to evidence in support of exercise related telomerase activity, a recent study found significantly raised hTERT mRNA levels in WBCs 60' after 30' of exercise at 80% of VO 2max and also tendentially raised hTERT mRNA levels in distinct T lymphocyte subpopulations (Chilton et al, 2014). The same study also screened 1,300 miRNAs levels for changes.…”
Section: Evidence For Exercise Dependent Regulation Of Telomerase Actmentioning
confidence: 93%
See 4 more Smart Citations
“…As to evidence in support of exercise related telomerase activity, a recent study found significantly raised hTERT mRNA levels in WBCs 60' after 30' of exercise at 80% of VO 2max and also tendentially raised hTERT mRNA levels in distinct T lymphocyte subpopulations (Chilton et al, 2014). The same study also screened 1,300 miRNAs levels for changes.…”
Section: Evidence For Exercise Dependent Regulation Of Telomerase Actmentioning
confidence: 93%
“…As to investigations of leukocytes, which include lymphocytes, it must be taken into account that lymphocytes comprise various subsets, and that relative and absolute cell counts in a blood sample might change as response to exercise (Chilton et al, 2014). Additionally, changes of telomerase activity due to exercise may be confounded by lymphocyte activation and telomerase expression due to antigen contact (Weng, 2001).…”
Section: Methodology Methods and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations